Comparison of Polymerase Chain Reaction-Restriction Fragment Length Polymorphism, Immunohistochemistry, and DNA Sequencing for the Detection of IDH1 Mutations in Gliomas - Malueka, Rusdy Ghazali; Theresia, Emilia; Fitria, Fitria; Argo, Ibnu Widya; Donurizki, Aditya Dwi; Shaleh, Sabillal; Innayah, Meutia Rizki; Wicaksono, Adiguno Suryo; Dananjoyo, Kusumo; Asmedi, Ahmad; Hartanto, Rachmat Andi; Dwianingsih, Ery Kus (Asian Pacific journal of cancer prevention : APJCP, 2020)
IDH1 mutation shows diagnostic, prognostic, and predictive value in gliomas. Direct Sanger sequencing is considered the gold standard to detect IDH1 mutation. However, this technology is not available in most neuropathological centers in developing countries such as Indonesia. Immunohistochemistry (IHC) and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) have also been used to detect IDH1 mutation. This study aimed to compare DNA sequencing, IHC, and PCR-RFLP in detecting IDH1 mutations in gliomas. Research subjects were recruited from Dr. Sardjito Hospital. Genomic DNA was extracted from fresh or formalin-fixed paraffin-embedded samples of tumor tissue. DNA sequencing, PCR-RFLP and IHC were performed to detect IDH1 mutation. Sensitivity, specificity, and accuracy of PCR-RFLP and IHC were calculated by comparing them to DNA sequencing as the gold standard. Among 61 recruited patients, 13 (21.3%) of them carried a mutation in codon 132 of the IDH1 gene, as shown by DNA sequencing. PCR-RFLP and DNA sequencing have a concordance value of 100%. Meanwhile, the concordance value between IDH1 R132H IHC and DNA sequencing was 96.7%. The sensitivity, specificity, positive predictive values, negative predictive values, and accuracy for PCR-RFLP were all 100%. On the other hand, the sensitivity, specificity, and accuracy of IHC were 92.3%, 97.9%, and 96.7%, respectively. This study showed that both PCR-RFLP and IHC have high accuracy in detecting IDH1 mutation. We recommend a combination of PCR-RFLP and IHC to detect IDH1 mutation in resource-limited settings. .